Criminal Liability Towards Corporations Acting As Narcotics Traffickers In Indonesia - Muhammad Hatta; Sumiadi Sumiadi; Zulfan Zulfan; Johari Johari; Husni Husni; Mohd Zamre Mohd Zahir (International Journal of Law, Environment, and Natural Resources, 2023)
Corporate crime is often referred to as a crime committed by a legal entity or organization. Corporate involvement in criminal activity can enable criminal access to methods of production, storage, distribution, or trading. In the context of narcotics crime, corporations could play a significant role in the trafficking of narcotics through a variety of modus operandi including production, distribution, and sales to the general public. Therefore, corporation as a legal subject can be held accountable. This study uses a statutory approach and is normative (doctrinal). It solely employs secondary data and is processed qualitatively to describe facts, documents, information, and other data related to criminal liability for corporations as perpetrators of narcotics trafficking in Indonesia. The embodiment of criminal liability towards corporations as perpetrators of narcotics trafficking is regulated in several provisions, including Article 130 of Law No. 35 of 2009 concerning Narcotics as well as Articles 60 to 64 and Article 70 of Law No. 5 of 1997 concerning Psychotropics. The crime of narcotics distribution through corporation involves businesses or legal entities such as hospitals, health clinics, pharmacies and others. Revocation of business licenses can be used as punishment for those companies, while the management may also face further legal repercussions.